PELATIHAN PERLUASAN PEMASARAN PRODUK BIOFLOK BERBASIS DIGITAL - Rikky Wisnu Nugraha; Fahmi Reza Ferdiansyah; Rini Ratnaningsih; Vyse Shahieza Pramono; Muhamad Rizky Nurrohmat; Rudy Sofian (Jurnal Abdimas Bina Bangsa, 2023)
In the current era of digitalization, technology has become an absolute must for increasing productivity. Digital-based marketing can increase the dissemination of business information. Lamajang Village, Pangalengan District, Bandung Regency has advantages in the agricultural and livestock sectors. One of the loci in this activity is Saung Abah Ambu, which is an MSME that operates in the field of fish breeding using biofloc technology. Saung Abah Ambu has 16 biofloc ponds which are managed by 3 employees. Apart from that, Saung Abah Ambu has 10 partners in marketing the harvest. So far, marketing has only been done using conventional methods, namely coming directly to the location, apart from that, another problem is financial administration records which tend to be less well organized. Another thing is that some partners do not have business legality in running their business. The method used in this activity is to provide training and assistance in increasing understanding regarding the use of gadgets and social media in product marketing, training in financial administration records and assistance in creating business legality. The results of this activity are that 90% of partners understand the importance of gadgets in digital marketing, 70% of partners are skilled in using digital content, Saung Abah Ambu has access and understands how to record finances through the SimpanKas application, and finally several partners have registered their business and have a number. Parent Business